New Data on the Bivalved Arthropod Tuzoia From the Cambrian (Series 2, Stage 4) Guanshan Biota in Kunming, Yunnan, Southwest China - Wu, Yichen; Liu, Jianni (Frontiers in Earth Science, 2022)
The Guanshan Biota (Cambrian Series 2, Stage 4) is a typical Burgess Shale-type biota and is one of the most significant Cambrian Konservat-Lagerstätten from China. Tuzoia is a relatively common non-biomineralized bivalved arthropod from the Guanshan Biota and, stratigraphically, ranges from Cambrian Series 2 through the Miaolingian Series. Based on new specimens from the Longbaoshan Section of the Wulongqing Formation, this study distinguished and described in detail the Tuzoia in the Guanshan biota. Supplemental details about the larval stage of Tuzoia tylodesa were obtained and the ontogenetic pattern of T. tylodesa was revised. The confirmation of the presence of Tuzoia retifera and the first report of Tuzoia cf. canadensis in the Guanshan biota, as well as the confirmation of the presence of T. retifera and the first report of T. cf. canadensis out of Lurentia (in Gondwana), indicated that species communication between paleogeographic plates is possible.